Property taxes and dynamic inefficiency: A orrection of a "correction" - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2020)
According to Homburg's (2014) comment on Kim and Lee (1997), an ad-valorem property tax on land cannot cause dynamic ineffi ciency of equilibrium allocations in an overlapping-generations model unless the tax is "confiscatory", i.e., equal to or greater than land rents. With such a tax, Homburg claims, land would be intrinsically worthless and the market for land would be closed. The latter claims are invalid because, as a store of value, land can be traded at a positive price even if the net rate of return on land is negative.
Keywords: D9; E62; H21; 330; Property taxes; dynamic inefficiency; overaccumulation of capital; land